2008
DOI: 10.1634/stemcells.2007-0988
|View full text |Cite
|
Sign up to set email alerts
|

IFATS Collection: Identification of Hemangioblasts in the Adult Human Adipose Tissue

Abstract: The stromal-vascular fraction (SVF) of human adipose tissue contains, among other cell types, mesenchymal stem cells and precursors of adipocyte and endothelial cells. Here we show that, in addition, the nonhematopoietic fraction of the SVF has hematopoietic activity, since all types of hematopoietic colony-forming units (CFUs) developed when cultured in methylcellulose-based medium. This hematopoietic activity was restricted to the CD45 ؊ CD105 ؉ cell subset, well correlated with KDR ؉ cell content, and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Terminal differentiation of these cells results in de novo generation of BMP-derived adipocytes. Alternatively, hematopoietic stem cells (HSCs) that reside in adipose tissue (23)(24)(25) might also serve as a resident source of white adipocytes. However, there are arguments against this alternative model.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal differentiation of these cells results in de novo generation of BMP-derived adipocytes. Alternatively, hematopoietic stem cells (HSCs) that reside in adipose tissue (23)(24)(25) might also serve as a resident source of white adipocytes. However, there are arguments against this alternative model.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 1 report demonstrated that murine adipose-derived hematopoietic stem/ progenitor cells contain precursors committed to the mast cell lineage [17]. Another report demonstrated the existence of hemangioblasts in human AT that exhibit the capacity for hematopoietic and endothelial differentiation in vitro [18].…”
Section: /Cd206mentioning
confidence: 99%
“…27 However, it was suggested that transplanted SVF contributed to the rebound of endogenous hematopoiesis rather than its own hematopoietic functions in the recipients. Moreover, a recent report 28 revealed that cultured SVF contains hemangioblasts, which have a bipotential capacity to differentiate into both endothelial cells and hematopoietic cells in vitro. However, the study focused on the potency of cultured SVF for hematopoiesis in vitro, instead of freshly isolated SVF.…”
Section: Introductionmentioning
confidence: 99%